Pennogenin Induces Apoptosis in Colon Cancer HCT-116 Cells via Increasing Apoptotic Markers and Downregulating PI3K/AKT/mTOR Pathway - Zheng, Guangtao; Gao, Dan; Wang, Lei; Zhou, Ke (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Colon cancer is the third major type of cancer globally and the second most reason for cancer-associated mortality. Natural products (phytochemicals) are considered safer alternatives to treat colon cancer. Objectives In this work, we aimed at disclosing the anticancer activities of the pennogenin against the colon cancer cells. Materials and Methods The antioxidant properties of pennogenin were investigated using numerous free radical scavenging tests, including DPPH and FRAP assays. The cytotoxicity of pennogenin (at concentrations ranging from 1-50 μM) against both colon cancer HCT-116 cells and non-malignant Vero cells was evaluated using the MTT test. The oxidative stress markers were determined using assay kits. The levels of ROS production, MMP level, and apoptotic levels were examined using specific fluorescence staining techniques. The levels of apoptotic proteins, cyclin D1, and PI3K/AKT/ mTOR pathway protein levels were evaluated using corresponding assay kits. Results The pennogenin efficiently reduced the free radicals, as determined by various techniques. The HCT-116 cell growth was significantly reduced after treating them with pennogenin, but the Vero cell growth was not affected by the pennogenin. The pennogenin treatment significantly enhanced the ROS accumulation, reduced the MMP, and induced cell death in the HCT-116 cells. The pennogenin treatment also elevated the levels of TBARS and reduced the antioxidant levels in the HCT-116 cells. Furthermore, the pennogenin also increased the apoptotic protein levels and reduced the cyclin D1 and PI3K/AKT/mTOR protein levels in the HCT-116 cells. Conclusion The outcomes of this study highlighted that pennogenin successfully suppresses cell growth and enhances cell death in HCT-116 cells by increasing oxidative stress markers, apoptotic protein levels, and blocking of PI3K/AKT/mTOR pathway. As a result, it was clear that the pennogenin has the capacity to be an effective anticancer agent for effectively treating colon cancer.
Keywords: PI3K/AKT/mTOR pathway; Pennogenin; Apoptosis; Cyclin D1; HCT-116 cells.